Forging Napoleon's Grande Armée motivation, military culture, and masculinity in the French army, 1800 - 1808 - Hughes, Michael J. (Warfare and culture series, 2012)
Introduction : military culture and motivation in the armies of Napoleon -- From the coasts of the ocean to the snows of Poland : the grande Armée and Napoleonic military culture -- Honneur, gloire, et patrie : honor in Napoleon's legions -- Imperial virtue : the evolution of French patriotism -- Napoleon's manhood : sex and martial masculinity in the French army -- Clothing the new emperor : creating the cult of Napoleon -- The emperor's grognards : the officer corps -- Devoted soldiers and reluctant conquerors : the rank-and-file -- Conclusion : vive l'empereur! : sustaining motivation in the armies of Napoleon, 1803-1808